A new species of the genus Anthaxia (Anthaxia) (Coleoptera: Buprestidae) from Republic of South Africa - Obořil, Martin; Baňař, Petr (Zootaxa, 2015)
Anthaxia (Anthaxia) kamieserrima sp. nov., a new endemic species from Republic of South Africa is described. New synonymy of Anthaxia (Anthaxia) aterrima Kerremams, 1903 (= Anthaxia (Anthaxia) braunsi Obenberger, 1922 syn. nov.) is proposed. Lectotypes and paralectotypes of A. aterrima and A. braunsi are designated.